The S-content-dependent lattice structure evolution and bandgap modulation in quaternary MgZnOS alloy films. (23rd November 2020) - Cheng, Hailing; Li, Lei; Wang, Yang; Lu, Yinmei; Zhang, Zaoli; Li, Mingkai; Klar, Peter J; He, Yunbin
Abstract: Bandgap engineering of ZnO by alloy formation is of great importance for its application in modern optoelectronic devices. Herein, Mg and S co-substituted quaternary Mg0.12 Zn0.88 O1− y S y (MgZnOS) alloy films with various S content were grown on c -plane sapphire by pulsed laser deposition using a Mg0.12 Zn0.88 O0.18 S0.82 ceramic target under various O2 partial pressures. The S-content-dependent phase structure evolution and S solubility limits in single-phase MgZnOS alloys were determined, and the correlation of lattice constants and band gap with the S content of the single-phase MgZnOS was quantitatively established. It turns out that the MgZnOS films grow quasi-epitaxially on c -sapphire with a wurtzite structure, which evolves intricately with varying S content. The S-rich MgZnOS films assume both lattice constants and in-plane orientation similar to those of ZnS. With decreasing S content, the alloy lattice first contracts along the out-of-plane direction, then shrinks in-plane, and partly re-orients by 30° in-plane, eventually approaching ZnO for the O-rich MgZnOS films. S content ( y S ) achieved in the single-phase O-rich and S-rich Mg0.12 Zn0.88 O1− y S y films is y S ⩽ 0.33 and y S ⩾ 0.67, respectively, far beyond the S solubility limits in the counterpart ternary ZnOS. While phase separation of MgZnO and MgZnS takes place in the films with S content between 0.34–0.65, in-plane domain separation with mutual rotation by 30° occurs in the O-rich single-phase MgZnOS films with y S ⩽ 0.08. Moreover, for the O-rich single-phase MgZnOS films, the lattice constant c expands linearly while a remains almost invariant with increasing S content. The band gap of MgZnOS is nonlinearly adjustable in the range of 3.13–3.66 eV, with a bowing parameter (∼1.89 eV) smaller than that of ZnOS (∼3.0 eV). The S-content-dependent evolutions of both lattice constants and band gap of MgZnOS differ distinctly from those of ZnOS, indicating bright prospects for synergistic Mg and S co-substitution in the effective modulation of both structure and band gap of ZnO to meet specific applications.